Estrutura e dinâmica familiar no estágio tardio do ciclo vital e deficiência intelectual - Takebayashi, Renata Balieiro [UNIFESP] (2017)
To know and understand the dynamics of a family including a member with Intellectual Disability in the late life cycle stage. Method: This was a qualitative clinical study. Ten families that took part in semistructured interviews were chosen. The interviews were complemented with genograms and ecomaps, and then content and thematic analysis was performed. The Systems Theory was used as theoretical referential and the Calgary Model for Family Evaluation (MCAF), as the methodologic referential. Results: Based on interviews with families, the following categories were developed: Family’s interaction with Intellectual Disability; Communication as a family strategy to share feelings and notice the other person; The perception of family isolation and the need of external aid; Family’s concern about future care: aging and death; and Interview as a tool to increase family communication and future reflections. Conclusion: Families including a person with Intellectual Disability face changes in their dynamics, structure and organization; they deal with difficulties regarding the social inclusion of the person with Intellectual Disability; and use specific mechanisms of communication and support search, in addition to the suffer they face towards future projections